Utilization of Different Omic Approaches to Unravel Stress Response Mechanisms in the Parasite Entamoeba histolytica - Nagaraja, Shruti; Ankri, Serge (Frontiers in Cellular and Infection Microbiology, 2018)
During its life cycle, the unicellular parasite Entamoeba histolytica is challenged by a wide variety of environmental stresses, such as fluctuation in glucose concentration, changes in gut microbiota composition, and the release of oxidative and nitrosative species from neutrophils and macrophages. The best mode of survival for this parasite is to continuously adapt itself to the dynamic environment of the host. Our ability to study the stress-induced responses and adaptive mechanisms of this parasite has been transformed through the development of genomics, proteomics or metabolomics (omics sciences). These studies provide insights into different facets of the parasite’s behaviour in the host. However, there is a dire need for multi-omics data integration to better understand its pathogenic nature, ultimately paving the way to identify new chemotherapeutic targets against amebiasis. This review provides an integration of the most relevant omics information on the mechanisms that are used by E.histolytica to resist environmental stresses.